2001
DOI: 10.1177/000348940111001203
|View full text |Cite
|
Sign up to set email alerts
|

Cell Biology of Laryngeal Epithelial Defenses in Health and Disease: Preliminary Studies

Abstract: Esophageal epithelium has intrinsic antireflux defenses, including carbonic anhydrases (CAs I to IV) that appear to be protective against gastric reflux. This study aimed to investigate the expression and distribution of CA isoenzymes in laryngeal epithelium. Laryngeal biopsy specimens collected from the vocal fold and interarytenoid regions were analyzed by Western blotting and immunofluorescence. Carbonic anhydrases I and II were expressed by the majority of samples analyzed. In contrast, CA III was differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 70 publications
3
97
0
9
Order By: Relevance
“…While it is reported that pH drops below 4 are associated with oesophageal damage, it is recognised that the deleterious actions of pepsin can occur with pH levels as high as 6 [17]. Previous studies have suggested that 50 episodes of reflux are at the upper limits of normal, however three episodes of laryngeal reflux over a week are capable of leading to significant damage in the laryngeal area [23,25,26,27].…”
Section: Pathophysiology: Current Conceptsmentioning
confidence: 99%
“…While it is reported that pH drops below 4 are associated with oesophageal damage, it is recognised that the deleterious actions of pepsin can occur with pH levels as high as 6 [17]. Previous studies have suggested that 50 episodes of reflux are at the upper limits of normal, however three episodes of laryngeal reflux over a week are capable of leading to significant damage in the laryngeal area [23,25,26,27].…”
Section: Pathophysiology: Current Conceptsmentioning
confidence: 99%
“…Therefore, LPR symptoms might arise, before severity of acidic reflux is not sufficient to induce development of esophagitis. [12] Contrary to GER, complaints of heartburn and regurgitation are not frequently encountered in LPR. [13,14] Ossakow et al [11] reported that patients with complaints of reflux had been either treated in the outpatient clinics of ENT (earnose and throat) (n=63) or gastroenterology (GE) (n=36).…”
Section: Discussionmentioning
confidence: 99%
“…Katalizuje ona proces odwracalnej hydratacji dwutlenku węgla a produktem reakcji są między innymi jony wodorowęglanowe alkalizujące środowisko. Wykazano, Ŝe u chorych z LPR ilość CA III spada w przednim odcinku krtani przy jednoczesnym wzroście w tylnym spoidle [119]. Wysunięto hipotezę, Ŝe właśnie duŜa koncentracja CA III w tylnym spoidle krtani moŜe zapobiegać rozwojowi raka, gdyŜ, jak powszechnie wiadomo, rak w tylnym odcinku krtani rozwija się bardzo rzadko [114].…”
Section: H Patofizjologia Lprunclassified